Proceso de atención de enfermería en adulto joven con dengue más colecistitis. - Condor Loor, Aranza Mishell (2024)
Dengue is an infectious viral pathology that is transmitted to humans through the bite of a contaminated mosquito; this is more common in tropical and subtropical regions. The complications of this pathology will depend on the care provided to the patient; dengue is classified as without warning signs, with warning signs, and severe dengue. The present case deals with a young adult with dengue plus cholecystitis, the main objective of which is to apply the nursing care process to the young adult. A cross-sectional bibliographic review was carried out in which dengue will be focused as the main pathology that affects young adults followed by cholecystitis since it is a complication that triggers dengue. Among the results and conclusions, it was possible to apply the nursing care process in a timely manner, it is a very useful tool and one of the most used methods, through which positive results are achieved in the patient's recovery.